Human-derived air-liquid interface cultures decipher Alzheimer's disease-SARS-CoV-2 crosstalk in the olfactory mucosa - Shahbaz, Muhammad Ali; Kuivanen, Suvi; Lampinen, Riikka; Mussalo, Laura; Hron, Tomáš; Závodná, Táňa; Ojha, Ravi; Krejčík, Zdeněk; Saveleva, Liudmila; Tahir, Numan Ahmad; Kalapudas, Juho; Koivisto, Anne M; et al. (Journal of neuroinflammation, 2023)
BACKGROUND: The neurological effects of the coronavirus disease of 2019 (COVID-19) raise concerns about potential long-term consequences, such as an increased risk of Alzheimer's disease (AD). Neuroinflammation and other AD-associated pathologies are also suggested to increase the risk of serious SARS-CoV-2 infection. Anosmia is a common neurological symptom reported in COVID-19 and in early AD. The olfactory mucosa (OM) is important for the perception of smell and a proposed site of viral entry to the brain. However, little is known about SARS-CoV-2 infection at the OM of individuals with AD. METHODS: To address this gap, we established a 3D in vitro model of the OM from primary cells derived from cognitively healthy and AD individuals. We cultured the cells at the air-liquid interface (ALI) to study SARS-CoV-2 infection under controlled experimental conditions. Primary OM cells in ALI expressed angiotensin-converting enzyme 2 (ACE-2), neuropilin-1 (NRP-1), and several other known SARS-CoV-2 receptor and were highly vulnerable to infection. Infection was determined by secreted viral RNA content and confirmed with SARS-CoV-2 nucleocapsid protein (NP) in the infected cells by immunocytochemistry. Differential responses of healthy and AD individuals-derived OM cells to SARS-CoV-2 were determined by RNA sequencing. RESULTS: Results indicate that cells derived from cognitively healthy donors and individuals with AD do not differ in susceptibility to infection with the wild-type SARS-CoV-2 virus. However, transcriptomic signatures in cells from individuals with AD are highly distinct. Specifically, the cells from AD patients that were infected with the virus showed increased levels of oxidative stress, desensitized inflammation and immune responses, and alterations to genes associated with olfaction. These results imply that individuals with AD may be at a greater risk of experiencing severe outcomes from the infection, potentially driven by pre-existing neuroinflammation. CONCLUSIONS: The study sheds light on the interplay between AD pathology and SARS-CoV-2 infection. Altered transcriptomic signatures in AD cells may contribute to unique symptoms and a more severe disease course, with a notable involvement of neuroinflammation. Furthermore, the research emphasizes the need for targeted interventions to enhance outcomes for AD patients with viral infection. The study is crucial to better comprehend the relationship between AD, COVID-19, and anosmia. It highlights the importance of ongoing research to develop more effective treatments for those at high risk of severe SARS-CoV-2 infection.
Keywords: Immune responses; COVID-19; Olfactory Mucosa; Air–liquid interface; Alzheimer’s disease; Alzheimerova nemoc; Alzheimer Disease; Neuroinflammatory Diseases; Neurological manifestations; lidé; čichová sliznice; Inflammation; Olfactory; Humans; Anosmia; anosmie; neurozánětlivé nemoci; SARS-CoV-2